New Photosensitizers for Photodynamic Therapy in Gastroenterology - SG Bown; AZ Rogowska (Canadian Journal of Gastroenterology)
Most applications of photodynamic therapy (PDT) in gastroenterology to date have used porfimer sodium as the photosensitizing agent. For destroying small lesions in the wall of the gastrointestinal tract in inoperable patients, it has proved to be most effective, but attempts to achieve circumferential mucosal ablation, as in the treatment of Barrett’s esophagus, have led to a high incidence of strictures, and all patients have cutaneous photosensitivity, which can last up to three months. Two new photosensitizers are of particular interest to gastroenterologists. PDT with metatetrahydroxyphenyl chlorin produces a similar biological effect as PDT with porfimer sodium, but the light doses required are much smaller, and cutaneous photosensitivity lasts only two to three weeks. Further, it can be used with percutaneous light delivery to destroy localized pancreatic cancers. The photosensitizing agent 5-amino levulinic acid, converted in vivo into the photoactive derivative protoporphyrin IX, sensitizes the mucosa much more than the underlying layers. This makes it feasible to destroy areas of abnormal mucosa without damaging the underlying muscle and is, therefore, better for treating Barrett’s esophagus. Detailed clinical studies are required to establish the real role of PDT with the use of these and other new photosensitizers.